ALIGNING MANAGEMENT OF APPLIED EDUCATION PROGRAMS IN INFORMATION AND COMMUNICATION TECHNOLOGY WITH GRAPHIC DESIGN INDUSTRY NEEDS TO ENHANCE STUDENT COMPETENCIES - Moh. Badruddin Amin; Hilmi Qosim Mubah (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2025)
Aligning vocational education management with contemporary creative industry demands is crucial for successful technological integration. This study describes managing applied information and communication technology education programs to enhance student competencies in graphic design at a state Islamic senior high school in Pamekasan. Employing a qualitative phenomenological approach, data were gathered through in-depth interviews, observations, and documentation involving school leaders, program managers, and students. Data analysis followed Miles, Huberman, and Saldana's model. Results indicate program management consists of planning, implementation, and evaluation. Planning involves identifying student needs and curricula based on industry partner guidelines. Implementation focuses on project-based learning to foster creativity and technical skills within collaborative teams. Evaluation occurs continuously through partner cooperation, encompassing formative and summative assessments plus competency certification. Despite challenges like limited facilities and motivation drops, collaborative strategies involving time management and instructional innovation were applied. This research contributes to developing adaptive applied education models responsive to workforce dynamics.